O uso de substâncias psicoativas na adolescência e a relação com as atitudes parentais - Cerutti, Fernanda (2014)
The general goal of this thesis was to investigate the relation between parental attitudes and drug abuse in adolescence. For that, it was carried out one theoretical study and one empirical; both have been presented as scholarly papers. By means of a systematic literature review, the theoretical study aimed to do an overview of the impacts that parent-child relation have on adolescents‟ development, regarding drug abuse. The studies included in the literature review covers a sample with a meaningful number of participants representing different countries. So, findings points out that parental attitudes represents a model for the child, also observing their attitudes, demonstrate affection and have a close relationship are effectiveness in prevention of drug abuse in adolescence. Additionally, the empirical study aimed to analyze the relation between adolescents' perceptions of parental attitudes and their trend to psychoactive substances abuse. For this purpose, a quantitative cross-sectional study was carried out; it composes a sample of 487 adolescents attending the last years of primary school and high school from public and private schools from the countryside in Rio Grande do Sul. All participants have completed a socio-demographic questionnaire - the ASSIST which investigates the drug abuse, and the PBI about adolescents' perceptions of parental attitudes. For statistical analysis, in addition to the descriptive analysis, it was applied the Multinomial Logistic Regression model adjusted with the Stepwise method, which have proposed models giving the probability of association between categories: no use; use; abuse and dependence of the nine drugs included in the study, with some socio-demographic data and with parenting styles and types of mother and father bonds. The Cronbach alpha coefficient was used to estimate the reliability of the questionnaires. Also, the models covered by the analysis were adjusted to three classes of drugs: tobacco, alcohol and marijuana. And, for each drug category were linked variables with higher influence in the use, abuse or dependence of the substance. Moreover, it was found that parenting style, affection or controlling (from mother or father), was presented in the three models. Summing up, the findings have shown the importance of studies analyzing the relation between drug abuse in adolescence and the adolescents' perceptions of parental attitudes.